THE ADEQUACY IN USING GAMES - Fazliddinovna, Islomova Latofat (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
Games are highly motivating since they are amusing and at the same time challenging. Furthermore, they employ meaningful and useful language in real contexts. They also encourage and increase cooperation. Games are highly motivating because they are amusing and interesting. They can be used to give practice in all language skills and be used to practice many types of communication.